2010
DOI: 10.1007/s10532-010-9371-y
|View full text |Cite
|
Sign up to set email alerts
|

An aminotransferase from bacterium ATCC 55552 deaminates hydrolyzed fumonisin B1

Abstract: Previous research identified several microorganisms and pathways capable of degrading the mycotoxin fumonisin B₁ (FB₁). Degradation of FB₁ by microorganisms seems to comprise two essential steps: hydrolysis to hydrolyzed fumonisin B₁ (HFB₁) and deamination of the hydrolysis product. One of the previously studied microorganisms was the Gram negative bacterium ATCC 55552. The gene corresponding to the first step of FB₁ degradation in this bacterium was identified, but the genetic basis for deamination of the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
(12 reference statements)
0
23
0
Order By: Relevance
“…Previous research identified degradation of FB1 by microorganisms is likely composed of two essential steps: hydrolysis to hydrolyzed fumonisin B1 (HFB1) and deamination of the hydrolysis product (Heinl et al, 2011). Benedetti et al (Benedetti et al, 2006) demonstrated that different bacterial isolates of maize ecosystem have the ability to degrade FB1, among of which, Sphingomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research identified degradation of FB1 by microorganisms is likely composed of two essential steps: hydrolysis to hydrolyzed fumonisin B1 (HFB1) and deamination of the hydrolysis product (Heinl et al, 2011). Benedetti et al (Benedetti et al, 2006) demonstrated that different bacterial isolates of maize ecosystem have the ability to degrade FB1, among of which, Sphingomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…MTA144, isolated from composted earth [92]. In this strain the two key DEs were identified within a gene cluster: fumD , encoding a type B carboxylesterase, and fumI , encoding an aminotransferase [80,93,94]. The authors also demonstrated the degrading activities of the two recombinant enzymes by in vitro assays.…”
Section: Mycotoxin Biotransformation By Enzymesmentioning
confidence: 99%
“…For example, fumonisin biodegradation was observed through the elimination of the tricarballylate side chains and amino groups. The enzymatic hydrolysis of such mycotoxins might involve carboxylesterases and aminotransferases from bacteria such as Sphingomonas and Sphingopyxis normally found in soil, which have the ability to detoxify recalcitrant persistent organic pollutants (PoPs) such as polycyclic aromatic hydrocarbons (PAHs) [40][41][42][43]. Other researchers have reported degradation or detoxiication of fumonisin, including by-products, by oxidative deaminase from Exophiala sp., a common soil organism [42][43][44].…”
Section: Biological Reduction Of Mycotoxinsmentioning
confidence: 99%